Systemic lupus erythematosus: history and modernity - E. L. Nasonov; S. K. Soloviev; A. V. Arshinov (Научно-практическая ревматология, 2022)
Systemic lupus erythematosus (SLE) is a systemic autoimmune rheumatic disease of unknown etiology, characterized by hyperproduction of non-organ-specific autoantibodies to various components of the cell nucleus and the development of immune-inflammatory damage to internal organs. Currently, SLE is considered as a prototype of a systemic human autoimmune pathology, the central mechanism of immunopathogenesis of which is a violation of immunological tolerance to self-antigens, due to a complex interaction of genetic, epigenetic, environmental factors. The publication discusses the history of the study of SLE, the contribution of Russian scientists (V.A. Nasonova and others) to the study of th is problem, current trends in clinical and scientific research related to the improvement of diagnostic criteria and pharmacotherapy of this disease.